Optimized degradation of doxycycline in aqueous systems using calcium peroxide nanoparticles via response surface methodology - Amerhaider Nuar, Nurul Nazihah; Md Jamil, Siti Nurul Ain; Choong, Thomas Shean Yaw; Mahadzir, Syazana Ishami; Mat Azmi, Intan Diana; Mohd Basri, Mohd Salahuddin; Abdul Hamid, Mohamad Rezi (American Chemical Society, 2025)
The presence of antibiotic residues in aqueous systems, particularly doxycycline (DOX), is harmful to the environment and public health. In this study, dextran-coated calcium peroxide nanoparticles (DEX@nCPs(DEX)), Fe(II), and oxalic acid (OA) were combined to improve the heterogeneous Fenton-like degradation of DOX. X-ray photoelectron spectroscopy (XPS) demonstrated the successful synthesis of DEX@nCPs(DEX), showing the presence of Ca, O, and C functional groups associated with dextran. Using response surface methodology with a central composite design (RSM-CCD), the optimal conditions (DEX@nCPs(DEX) dosage: 2 g/L, pH: 5, contact time: 420 min) achieved 90% DOX removal, which was 20% higher than using DEX@nCPs(DEX)/Fe(II) alone. The degradation process followed first-order kinetics with a rate constant of k1 = 0.0047 min-1. Model validation showed high predictive accuracy (R2 = 0.996; adjusted R2 = 0.987). Scavenger and photoluminescence analyses revealed hydroxyl radicals (•OH) to be the primary reactive species, accounting for over 80% of the degradation activity. The DEX@nCPs(DEX)/Fe(II)/OA system offers a promising approach for mitigating pharmaceutical pollutants in water, contributing to more sustainable environmental management practices.